MODEL ARUS JENUH DASAR PADA SIMPANG BERSINYAL (STUDI KASUS PADA SIMPANG DENGAN LENGAN EFEKTIF SATU DAN DUA LAJUR DI BANDA ACEH) - Muntazar Muntazar; Muhammad Isya; Sugiarto Sugiarto (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2017)
Isolated signalized intersection plays an important role in distributing traffic movements at intersection. The main functions of the intersection are not only to reduce potential conflicts of flow (safety) but also to avoid concentrations of flow (breakdowns). An Optimal operation of intersection becomes the main focus of traffic experts as consequence of the worsening traffic condition due to highly private vehicle usage. Using video tape data recorded in Banda Aceh, therefore, this study aims to explore the influence of exogenous variables such as the intersection geometric and the traffic composition on determining base saturation flow rate at medium size signalized intersection. In this study, the concept of non-lane based traffic movement is used to observe interactions and movements among vehicles within traffic. Synchronous linear regression (SLR) approach is further applied to model and calibrate unknown model parameters. Two models are proposed in this study including without and with intercept. Findings from empirical results show that SFR models are So=421W and So=811+292W for the model without and with intercept, respectively. Results from validation further reveals that RMSPE value is about 0.8-2.6% and RMSE approximately 202-337 PCU/hr.Noted that proposedmodels are only valid for medium size intersection with effective legswidth to be varied from 3 to 8m.Abstrak: Simpang memiliki peranan penting dalam menyalurkan pergerakan lalu lintas dari berbagai pertemuan arus pergerakan di persimpangan. Fungsi utama simpang adalah mengurangi potensi konflik (safety) dan mengurangi konsentrasi arus (breakdown). Pengoperasian simpang yang optimal menjadi focus utama para ahli rekayasa lalu lintas seiring dengan memburuknya operasional lalu lintas yang disebabkan tingginya pengguna kendaraan pribadi. Menggunakan video data yang direkam di Banda Aceh, penelitian ini bertujuan mengekplorasi pengaruh variable eksogen seperti layout geometric simpang dan komposisi aliran lalu lintas terhadap arus jenuh dasar pada simpang bersinyal terisolasi. Konsep pergerakan kendaraan perlebar efektif lengan simpang (non-lane based movement) digunakan untuk mengamati interaksi dan pergerakan antar kendaraan. Metode Synchronous linear regression (SLR) digunakan untuk memodelkan dan mengkalibrasi koefisien model. Dua model diusulkan pada penelitian ini, yaitu dengan dan tanpa konstanta intercept. Dari hasil empiris diperoleh So=421W untuk model tanpa intercept dan So=811+292W dengan intercept. Dari hasil validasi menunjukkan RMSPE sebesar 0.8-2.6% dan RMSE sekitar 202-337 SMP/jam. Model ini valid untuk simpang dengan lebar efektif lengan simpang bervariasi dari 3-8m.